The Possible Effect of Celastrol on Ameliorating Mitochondrial Dysfunction and Neuro-inflammation in Sodium Valproate Induced- Rat Model of Autism - AmlAlaa El-Din El-Sayed Ahmed; Samia HussienAbou El-Seoud; Fleur Fathi Abdel Moneim; Rasha Osama El-Esawy (Institute of Medico-legal Publications Pvt Ltd, 2022)
Autism spectrum disorder (ASD) is a neurodevelopmental disease with impairment in social interactions,language and repetitive stereotypical behaviors. Celastrol is a natural safe compound that has antiinflammatoryand as a neuroprotective effects. 48 male offspringswistar rats divided into 6 groups;normal control group, offsprings receive vehicle, autistic offsprings receive vehicle, autistic offspringsreceive risperidone, autistic offspringsreceive celastrol, autistic offspringsreceive both risperidone&celastrol. At the end of experiment behavioral tests were performed then neurochemical analysisand histopathological examination. The obtained data showed that celastrol improved social deficits,decreased repetitive/restricted behaviors in T-maze test, significant increase in SIRT-1, GSH levelwith significant decrease in DRP-1, IL-6, caspase-3 and MDA with amelioration of histopathologicalfindings in VPA-induced ASD in both cerebellum and hippocampus. These findings pave the way forusing celastrol as an adjuvant therapy during long-term clinical use of risperidone in ASD.